Fiber-toughened transparent microcrystalline glass and preparation method thereof
By adding inorganic fibers in the preparation process of transparent microcrystalline glass and undergoing special high-temperature treatment to form a fiber mesh structure, the problem of insufficient scratch resistance in the existing glass is solved, and higher scratch resistance and other excellent physical properties are achieved.
Patent Information
- Application Number
- CN202411964271.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-07
AI Technical Summary
The existing transparent microcrystal cover glass has insufficient scratch resistance in practical applications and the microcrystal structure control is not mature enough, resulting in easy generation and expansion of scratches.
A fiber-toughened transparent microcrystalline glass preparation method is adopted. By uniformly mixing raw materials at high temperatures, controlling the melting curve to add inorganic fibers, and performing multi-stage insulation and crystallization treatment, a fiber mesh structure is formed to improve the scratch resistance of the glass.
The scratch resistance of transparent microcrystalline glass is significantly improved, and the maximum scratch width performs better than the prior art under different pressures, and maintains high light transmittance, low coefficient of expansion and good impact resistance.
Smart Images

Figure BDA0005217951890000111 
Figure BDA0005217951890000121 
Figure BDA0005217951890000131
Abstract
Description
Technical Field
[0001] The present application relates to the field of glass, and more specifically, to a fiber-reinforced transparent microcrystalline glass and a preparation method thereof. Background Art
[0002] In today's consumer electronics and display technology fields, transparent microcrystalline cover glass, as a key material, has broad application prospects. Due to its excellent light transmittance and mechanical strength, it is widely used in screen protection for smartphones, tablets and various smart wearable devices. With the advancement of technology, people's demand for electronic products is growing, which has promoted the continuous innovation and development of transparent microcrystalline cover glass technology. However, in practical applications, the scratch resistance of transparent microcrystalline cover glass has always been a key problem that needs to be solved urgently.
[0003] At present, in order to improve the scratch resistance of transparent microcrystalline cover glass, the industry generally adopts a variety of methods. Common methods include: (1) improving the raw material formula to enhance the hardness of the glass itself; (2) using high temperature annealing treatment to optimize the microstructure inside the glass and reduce internal stress; (3) performing chemical strengthening treatment on the glass surface, such as ion exchange method, to form a compressive stress layer; (4) using laser etching technology to improve surface flatness and reduce the possibility of scratches.
[0004] Although these methods can improve the scratch resistance of transparent microcrystalline cover glass to a certain extent, they still have certain limitations. The control technology of the microcrystalline structure is not mature enough. During the preparation process, the growth and distribution of microcrystalline are difficult to accurately control, resulting in unsatisfactory interface bonding between microcrystalline and glass phase. Especially when scratched by hard objects from the outside, these uneven interfaces easily become stress concentration areas, making scratches more likely to occur and expand. Therefore, existing technical means still cannot fully meet the market demand for highly scratch-resistant transparent microcrystalline cover glass. Summary of the invention
[0005] In order to solve the above technical problems, the present application provides a fiber-reinforced transparent microcrystalline glass and a preparation method thereof.
[0006] This application adopts the following technical solutions:
[0007] A method for preparing a fiber-reinforced transparent microcrystalline glass, wherein the light transmittance of the transparent microcrystalline glass at 550 nm of visible light is above 92%, and the maximum scratch width of the transparent microcrystalline glass under a pressure of 1.0 kg is below 13.07 μm; the maximum scratch width under a pressure of 1.8 kg is below 22.25 μm; the maximum scratch width under a pressure of 2.3 kg is below 35.58 μm; and the maximum scratch width under a pressure of 2.8 kg is below 51.17 μm.
[0008] The preparation method comprises:
[0009] Prepare raw materials according to the oxide formula, pour the raw materials into a mixer for mixing to obtain a mixed material, and determine whether the mixed material is homogenized by testing the conductivity of the mixed material;
[0010] The homogenized mixed material is loaded into a platinum crucible, and then the platinum crucible is placed in a high-temperature lifting furnace, and the mixed material is kept warm at a melting temperature of 1500-1600° C. for the first stage, and then the temperature is lowered to 1400-1450° C. for the second stage, and 0.5-2.0wt% of inorganic fiber is added, and the mixture is kept warm again for 5-20 minutes after being stirred evenly, and then the temperature is lowered to 1300-1350° C. for the third stage to obtain a glass melt;
[0011] After the glass melt is cast into shape, it is annealed, crystallized and chemically strengthened to obtain transparent microcrystalline glass.
[0012] Furthermore, the heating rate of the high temperature lifting furnace is 5-10°C / min when reaching the melting temperature of 1500-1600°C, and the insulation time of the first stage is 2-3h.
[0013] Furthermore, the time for the temperature in the high-temperature lifting furnace to drop from the melting temperature of 1500-1600° C. to 1400-1450° C. is 20-30 minutes.
[0014] Furthermore, before adding the inorganic fiber, the second stage heat preservation time is 0.5-1h; then the temperature is lowered to 1300-1350°C for the third stage heat preservation time of 5-10min.
[0015] Furthermore, the inorganic fiber is selected from any one or more of glass fiber, basalt fiber and zirconia fiber, and the diameter of the inorganic fiber is 20-50 nm.
[0016] Furthermore, the annealing temperature is 500-550° C., and the holding time is 0.5-1 h.
[0017] Furthermore, the above crystallization treatment includes a nucleation stage and a crystallization stage. The temperature of the nucleation stage is 520-600° C., and the temperature is kept for 2-4 hours; the temperature of the crystallization stage is 700-800° C., and the temperature is kept for 3-5 hours.
[0018] Furthermore, the raw materials include quartz sand, alumina, soda ash, potassium carbonate, zirconium oxide, lithium carbonate, diammonium phosphate and sodium nitrate. The raw materials, calculated by mass percentage of oxides, include:
[0019] SiO 2 67-78%, Al2 O 3 5-10%, Na 2 O 0.5-2.1%, K 2 O 0.5-1.3%, ZrO 2 4.5-8.1%, Li 2 O8.7-12.5%, P 2 O 5 0.8-2.3%, NO 3 - 0.5-2%.
[0020] Furthermore, the above-mentioned test method for homogenizing the mixed material is: randomly sample 3-5 portions of the mixed material, each portion is 10-20g, and the samples are mixed with 100ml of pure water for 5-10min respectively, and the conductivity of each sample is tested, and the average value is calculated. If the difference between the conductivity of each sample and the average value is in the range of -0.25 to 0.25ms / cm, it indicates that the mixed material has been mixed evenly.
[0021] On the other hand, the present application also provides a fiber-reinforced transparent microcrystalline glass, which is prepared by the above-mentioned preparation method;
[0022] The maximum scratch width of transparent microcrystalline glass under a pressure of 1.0Kg is less than 13.07μm; the maximum scratch width under a pressure of 1.8Kg is less than 22.25μm; the maximum scratch width under a pressure of 2.3Kg is less than 35.58μm; and the maximum scratch width under a pressure of 2.8Kg is less than 51.17μm.
[0023] In summary, this application has the following beneficial effects:
[0024] 1. In the raw material mixing step of the preparation method of the present application, the conductivity of the mixed material is tested to determine whether the mixed material is homogenized. The mixing degree of the raw materials directly determines the uniformity of the glass after melting and the stability of the glass performance. By adopting this special raw material uniformity detection method, the present application can ensure that the raw materials are homogenized and mixed, thereby improving the stability of the glass performance.
[0025] 2. In the process of melting the raw materials, the present application controls the melting curve, adds the inorganic fiber raw materials in a suitable temperature range, and pays attention to the insulation time, so as to prevent the added inorganic fiber raw materials from being excessively melted under high temperature conditions, and the purpose of fiber toughening cannot be achieved. The length of the insulation time determines the content of the fiber raw materials in the glass after molding. The fiber content should not be too much, otherwise the glass will crack due to the inconsistency between the expansion rate of the fiber material and the matrix glass; and if the fiber content is too low, a fiber mesh structure cannot be formed inside the glass, thereby failing to improve the scratch resistance of the glass. The present application selects the raw material category of the inorganic fiber, controls the amount of inorganic fiber added, the addition temperature, and the insulation time after adding, so that the content of inorganic fiber in the glass is within an appropriate range, and makes it present a mesh interwoven structure in the glass, thereby improving the scratch resistance of the glass.
[0026] 3. The present application uses a special preparation process to obtain a transparent microcrystalline glass with significantly improved scratch resistance, which is specifically manifested in: the maximum scratch width under a pressure of 1.0Kg is 13.07μm, which is 1 / 4 to 1 / 3 of the current transparent microcrystalline; the maximum scratch width under a pressure of 1.8Kg is 22.25μm, which is 1 / 3 to 1 / 2 of the current transparent microcrystalline; the maximum scratch width under a pressure of 2.3Kg is 35.58μm, 1 / 3 to 1 / 2; the maximum scratch width under a pressure of 2.8Kg is 51.17μm, which is 1 / 3 to 1 / 2 of the current transparent microcrystalline. At the same time, the transparent microcrystalline glass obtained in the present application also has high light transmittance (its light transmittance at 550nm of visible light is above 92%), low expansion coefficient, high hardness, good impact resistance and strong chemical corrosion resistance, and can be applied to various display protective glasses. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is the melting curve of the method provided in this application;
[0028] Figure 2 This is an electron microscope image of the fiber-toughened transparent glass-ceramics provided in Example 1 of the present application;
[0029] Figure 3 This is an electron microscope image of the common transparent glass-ceramics provided in the comparative example of the present application;
[0030] Figure 4 This is a scratch test diagram of Example 1 of the present application, Comparative Example 1 and ordinary transparent micro-ceramic glass under a weight of 1.0Kg;
[0031] Figure 5 This is a scratch test diagram of Example 1 of the present application, Comparative Example 1 and ordinary transparent micro-ceramic glass under a weight of 1.8Kg;
[0032] Figure 6This is a scratch test diagram of Example 1 of the present application, Comparative Example 1 and ordinary transparent micro-ceramic glass under a weight of 2.3Kg;
[0033] Figure 7 This is a scratch test chart of Example 1 of the present application, Comparative Example 1 and ordinary transparent microcrystalline glass under a counterweight of 2.8Kg. DETAILED DESCRIPTION
[0034] The embodiments of the present invention will be described in detail below in conjunction with examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. The specific conditions not specified in the examples are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.
[0035] This embodiment provides a fiber-reinforced transparent glass-ceramics, and the preparation method thereof includes:
[0036] Step S1, preparing materials:
[0037] Raw materials are calculated by mass percentage of oxides, including: SiO 2 67-78%, Al 2 O 3 5-10%, Na 2 O 0.5-2.1%, K 2 O 0.5-1.3%, ZrO 2 4.5-8.1%, Li 2 O 8.7-12.5%, P 2 O 5 0.8-2.3%, NO 3 - 0.5-2%.
[0038] Preferably, the raw materials, measured by mass percentage of oxides, include: SiO 2 70-73%, Al 2 O 3 6-8%, Na 2 O1.0-1.9%, K 2 O 0.9-1.2%, ZrO 2 5.5-7.0%, Li 2 O 9.5-11.5%, P 2 O 5 1.1-1.8%, NO 3 - 0.9-1.5%.
[0039] Among them, SiO 2 Quartz sand or ultra-pure sand, Al2 O 3 Provided by alumina or aluminum hydroxide, Na 2 O is provided by soda ash, sodium carbonate or sodium oxide, K 2 O is provided by potassium carbonate or potassium hydroxide, ZrO 2 Provided by zirconium oxide or zircon sand, Li 2 O is provided by lithium carbonate, P 2 O 5 Provided by phosphorus pentoxide or diammonium phosphate.
[0040] The percentage of raw material mass is obtained by the oxide composition ratio and the oxide content in the raw material as shown in Table 1:
[0041] Table 1.
[0042] Raw material types Quartz sand Alumina soda ash Potassium carbonate Zirconia Lithium carbonate Ammonium dihydrogen phosphate Sodium nitrate Mass ratio (%) 52~65 5.2~7.5 0.8~2.5 0.5~1.8 5.2~7.6 18.3~25.4 2.1~3.6 0.6~1.2
[0043] The raw material formula is preferably composed of 58-63% quartz sand, 5.8-6.5% alumina, 1.5-2.3% soda ash, 0.5-1.3% potassium carbonate, 5.4-6.0% zirconium oxide, 20.0-24.0% lithium carbonate, 2.3-3.0% diammonium phosphate and 0.6-0.9% sodium nitrate according to the mass percentage.
[0044] Step S2, mixing:
[0045] The raw materials are poured into a mixer for mixing to obtain a mixed material, and the conductivity of the mixed material is tested to determine whether the mixed material is homogenized;
[0046] The mixer is a three-dimensional motion mixer, and the mixing time is 30-60 minutes.
[0047] Standard Test Methods for Homogenization Mixing:
[0048] Randomly sample 4 portions of the mixed raw materials, each of 10-20g, dissolve them in a beaker filled with 100mL of pure water, and stir with a stirrer for 5-10min. Insert the conductivity tester into the stirred beaker for 10-30S. After the values are stable, read the conductivity values H1, H2, H3, H4, and calculate the average Havg. If the difference between each conductivity and the average is within the range of ±0.25ms / cm, it indicates that the raw materials have been mixed evenly. The degree of mixing of the raw materials determines the uniformity of the glass after melting and the stability of its performance.
[0049] Step S3, raw material melting:
[0050] The homogenized mixed material is placed in a platinum crucible, and then the platinum crucible is placed in a high-temperature lifting furnace. Figure 1 The melting curve shown is for glass melting.
[0051] There are three insulation stages in the melting process, which are as follows:
[0052] (1) First stage insulation:
[0053] The melting temperature is set at 1500-1600°C, and the high-temperature lifting furnace is heated to the melting temperature at a heating rate of 5-10°C / min, and kept at this temperature for 2-3 hours to complete the melting and clarification of the batch materials and form a uniform and stable glass liquid.
[0054] (2) Second stage insulation:
[0055] After the first stage of insulation is completed, the temperature of the high-temperature lifting furnace is reduced to 1400-1450°C within 20-30 minutes, and the temperature is kept at this temperature for 0.5-1h. The purpose is: the melting point of inorganic fiber raw materials is generally 1450°C-1550°C, so the melting temperature is lowered to prevent the inorganic fiber raw materials from melting quickly at high temperature, resulting in the failure to achieve the purpose of fiber toughening; after the insulation is completed, the inorganic fiber is added, stirred with a platinum rod for 5-10S, and then kept warm for another 5-20 minutes to complete the second stage of insulation.
[0056] The inorganic fiber includes one or more of glass fiber, basalt fiber and zirconia fiber. The amount of the inorganic fiber introduced is 0.5-2.0wt%, preferably 0.7-1.8wt%. The diameter of the fiber is 20-50nm, and the fiber diameter cannot be greater than 50nm. 50nm is the maximum grain size of transparent microcrystalline glass. If it exceeds 50nm, the transmittance of the glass will be affected, and if it is less than 20nm, the fiber strength will be insufficient, and the toughening effect of the glass cannot be achieved.
[0057] After adding inorganic fiber raw materials, pay attention to the insulation time to prevent the inorganic fiber from being over-melted under high temperature conditions, so as to fail to achieve the purpose of fiber toughening. Methods for judging whether the fiber is over-melted: First, it is necessary to confirm the type of fiber used. The melting temperature of each fiber is different. For example, the melting temperature of basalt fiber is 1450-1500℃, and the melting temperature of glass fiber is 1500-1550℃. The insulation time is judged according to the melting temperature. Finally, to confirm whether the fiber is over-melted, it is necessary to break the melted glass and use a strong flashlight to observe whether there are abnormal bright spots at the fracture of the glass. If there are, it indicates that there are fiber raw materials here, which changes the refraction of light. The length of the insulation time determines the content of fiber raw materials in the glass after molding. The fiber content should not be too much, otherwise the glass will crack due to the inconsistency between the expansion rate of the fiber material and the matrix glass. If the fiber content is too low, it is impossible to form a fiber mesh structure inside the glass, thereby failing to improve the scratch resistance of the glass.
[0058] (3) The third insulation stage
[0059] After the second stage of heat preservation is completed, the temperature of the high-temperature lifting furnace is lowered to 1300-1350℃ within 10-20 minutes, and the temperature is kept at this temperature for 5-10 minutes to complete the melting process of the glass. The heat preservation in this stage is to ensure that the temperature of the glass liquid is uniform as a whole. If the glass liquid is directly formed after it drops to the target temperature, the temperature of the glass liquid will be unstable. The actual temperature of the glass liquid may be higher than the temperature displayed by the equipment, resulting in differences in the viscosity and composition of the formed glass.
[0060] Step S4, glass casting and molding:
[0061] Take out the platinum crucible through the clamp, and pour the glass liquid in the crucible into the square mold prepared in advance. The size of the mold is determined by the content of the glass liquid. The calculation method is as follows:
[0062] The density of general transparent microcrystalline glass is 2.4~2.5g / cm 3 The weight of the glass liquid is determined by the loss on ignition of the raw materials in the formula. Generally, the glass liquid yield accounts for 80-90% of the batch material. This method can be used to calculate the volume V of the glass after molding, thereby determining the size of the mold.
[0063] Step S5, glass annealing:
[0064] The formed glass block is placed in a muffle furnace, the annealing temperature is set at 500-550℃, and the temperature is kept for 0.5-1h. After the temperature is kept, it can be cooled with the furnace. When the annealed glass is irradiated with strong light, it can be observed that there are abnormally bright spots inside the glass, which further indicates the presence of fiber substances in the glass.
[0065] Step S6: Glass crystallization
[0066] After annealing, the glass is heated and crystallized according to the designed heat treatment system, so that a certain number of crystals grow inside the glass. The heat treatment system is: nucleation temperature 520 ~ 600 ℃, heat preservation 2 ~ 4h, crystallization temperature 700 ~ 800 ℃, heat preservation 3 ~ 5h, the whole process heating rate is 5 ~ 10 ℃ / min. At this time, the glass is a mixture of crystals, glass and fibers, and the fiber material is interwoven in the glass in a mesh form, thereby further strengthening the structure of the glass and resisting external scratches.
[0067] Step S7: further processing.
[0068] The glass blocks are cut into glass sheets with a thickness of 0.3-1.2 mm using wire cutting equipment, and the length and width are cut according to the requirements. After cutting, the glass edges are polished using CNC, and then the glass is strengthened once and twice to complete the deep processing of the glass.
[0069] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0070] Example 1
[0071] This embodiment provides a fiber-reinforced transparent glass-ceramics, the preparation method of which includes:
[0072] (1) The raw material formula is shown in Table 2:
[0073] Table 2.
[0074] Raw material types Quartz sand Alumina soda ash Potassium carbonate Zirconia Lithium carbonate Ammonium dihydrogen phosphate Sodium nitrate total Mass ratio (%) 60.0 6.0 2.0 0.5 5.8 22.5 2.5 0.7 100.0
[0075] (2) Raw material mixing:
[0076] Pour the prepared mixture into a three-dimensional motion mixer and mix evenly for 50 minutes. Randomly sample 4 portions, each with a mass of 10g, and pour them into 4 beakers filled with 100mL of pure water respectively. Stir with a stirrer for 10 minutes, insert the conductivity tester into the stirred beaker, test for 20 seconds, and read the conductivity values H1=102.36ms / cm, H2=102.28ms / cm, H3=102.45ms / cm, H4=102.31ms / cm after the values stabilize, and calculate the average Havg=102.35ms / cm. The difference between Havg and each conductivity value is -0.01ms / cm, -0.07ms / cm, 0.1ms / cm, and -0.04ms / cm, respectively. The difference is within the range of ±0.25ms / cm, indicating that the raw materials have been fully mixed.
[0077] (3) Melting process
[0078] The homogenized mixed material is loaded into a platinum crucible, and then the platinum crucible is placed in a high-temperature lifting furnace, the maximum melting temperature is set to 1550°C, and the temperature is kept for 3 hours with a heating rate of 10°C / min. After the insulation is completed, the temperature is reduced to 1450°C for 30 minutes and the temperature is kept for another 0.5 hour. After the insulation is completed, glass fiber (with a diameter of 35 nm) is added, and the temperature is kept again after stirring for 10 seconds with a platinum rod. After the insulation is completed, the temperature is reduced to 1350°C for 20 minutes, and finally the temperature is kept for another 10 minutes to complete the melting process of the glass.
[0079] (4) Glass casting
[0080] The platinum crucible is taken out by a clamp, and the glass liquid in the crucible is poured into a square mold prepared in advance for casting and molding.
[0081] (5) Annealing
[0082] The formed glass block is placed in a muffle furnace, the annealing temperature is set to 500°C, and the temperature is kept for 1 hour. After the temperature is kept, the glass can be cooled with the furnace. The annealed glass is irradiated with strong light to observe whether there is any luminous substance.
[0083] (6) Glass crystallization treatment
[0084] Heat treatment system: Heat treatment system: nucleation temperature 520℃, insulation for 3h, crystallization temperature 780℃, insulation for 4h, the heating rate of the whole process is 5℃ / min, and the glass after crystallization is cut, CNC, primary strengthening, secondary strengthening and other deep processing according to the required size.
[0085] (7) Performance testing
[0086] a. The transmittance was measured using a spectrophotometer in accordance with standard ISO13468-1:1996.
[0087] b. The final glass was scanned under a transmission electron microscope. The results were similar to Figure 2 As shown ( Figure 3 It is an ordinary transparent microcrystalline glass without added fibers). By comparison, it can be seen that in the transparent microcrystalline glass provided by the present application, it is clearly observed that the fiber material is interwoven in the glass in a network form.
[0088] c. The processed glass was subjected to scratch tests under 1.0Kg, 1.8Kg, 2.3Kg and 2.8Kg weights respectively: the scratch rate was 1mm / s. The scratched glass was analyzed under a polarizing microscope and the scratch width was marked. The test pictures are as follows Figure 4-7 shown.
[0089] The uniformity of scratches is judged as follows: the difference between the maximum scratch width and the minimum scratch width is expressed by the range: 1.0Kg range ≤3.0μm, 1.8Kg range ≤5.0μm, 2.3Kg range ≤10.0μm, 2.8Kg range ≤15.0μm.
[0090] Embodiment 2-4
[0091] The difference between this embodiment and embodiment 1 is that the raw material formula is different, as shown in Table 3:
[0092] Table 3.
[0093]
[0094] Example 5
[0095] The difference between this embodiment and embodiment 1 is (3) melting process:
[0096] The homogenized mixed material is loaded into a platinum crucible, and then the platinum crucible is placed in a high-temperature lifting furnace, the maximum melting temperature is set to 1600°C, and the temperature is kept for 2 hours with a heating rate of 5°C / min. After the insulation is completed, the temperature is reduced to 1450°C 20 minutes later, and the temperature is kept for 0.5 hours again. After the insulation is completed, glass fiber (with a diameter of 35nm) is added, and the temperature is kept again after stirring with a platinum rod for 10 seconds. After the insulation is completed, the temperature is reduced to 1300°C 20 minutes later, and finally the temperature is kept for 10 minutes to complete the melting process of the glass.
[0097] Example 6
[0098] The difference between this embodiment and embodiment 1 is (3) melting process:
[0099] The homogenized mixed material is loaded into a platinum crucible, and then the platinum crucible is placed in a high-temperature lifting furnace, the maximum melting temperature is set to 1500°C, and the temperature is kept for 2.5 hours, the heating rate is 8°C / min, and the temperature is reduced to 1450°C 25 minutes after the insulation is completed, and the temperature is kept for 0.5 hours again. After the insulation is completed, glass fiber (diameter 35nm) is added, and it is stirred with a platinum rod for 10 seconds and then kept again. After the insulation is completed, the temperature is reduced to 1350°C 10 minutes, and finally the temperature is kept for 5 minutes to complete the melting process of the glass.
[0100] Embodiment 7-14
[0101] The difference between this group of examples and Example 1 is that the content of the inorganic fiber material added, the temperature when the fiber is added, and the insulation time after the fiber is added are different, as shown in Table 4:
[0102] Table 4.
[0103]
[0104]
[0105] As shown in Table 4, when the inorganic fiber added in the second heat preservation stage is any one of glass fiber, basalt fiber and zirconia fiber, the fiber addition temperature is controlled at 1400-1450℃, and the temperature is kept for a certain period of time. When observing the glass fracture with a strong light flashlight, there are abnormal bright spots, indicating that the fiber is not over-melted. And the difference between the maximum scratch width and the minimum scratch width of the final glass is: 1.0Kg range ≤3.0μm, 1.8Kg range ≤5.0μm, 2.3Kg range ≤10.0μm, 2.8Kg range ≤15.0μm, indicating that the final glass has uniform scratch width and strong scratch resistance.
[0106] Examples 15-23
[0107] The difference between this group of examples and Example 1 is that two inorganic fiber materials are added (the total amount is 2.0wt%), the temperature when the fiber is added (1450°C) and the insulation time after the fiber is added are different, as shown in Table 5:
[0108] Table 5.
[0109]
[0110]
[0111] It can be seen from Table 5 that when the fiber adding temperature is controlled to 1450°C during the second stage of heat preservation, any two of glass fiber, basalt fiber or zirconia fiber are added in an amount of 2.0wt%, scratch-resistant transparent microcrystalline glass with uniform scratch width can be obtained.
[0112] Examples 24-26
[0113] The difference between this group of examples and Example 1 is that three inorganic fiber materials are added (the total amount is 2.0wt%), the temperature when the fiber is added (1450°C) and the insulation time after the fiber is added are different, as shown in Table 6:
[0114] Table 6.
[0115]
[0116]
[0117] It can be seen from Table 6 that when the fiber adding temperature is controlled at 1450°C during the second stage of heat preservation, three fiber raw materials are added at the same time: glass fiber, basalt fiber and zirconia fiber, and the addition amount is 2.0wt%, scratch-resistant transparent microcrystalline glass with uniform scratch width can be obtained.
[0118] Comparative Example
[0119] Comparative Examples 1-6
[0120] The difference between this group of comparative examples and Example 1 is the content of inorganic fiber material added, the temperature when the fiber is added (1450° C.) and the insulation time after the fiber is added, as shown in Table 7:
[0121] Table 7.
[0122]
[0123]
[0124] It can be seen from Table 7 that when the amount of inorganic fiber added is too little (0.2wt%), the scratch width of the glass is larger. This is mainly because the fiber content is too low and a fiber network structure cannot be formed inside the glass, resulting in the fiber toughening effect being not obvious. When the amount of inorganic fiber added is too much (2.5wt%), the glass is prone to expansion and cracking, and the scratch width is larger. This is mainly because the expansion rate of the fiber material is inconsistent with that of the matrix glass.
[0125] Comparative Examples 7-15
[0126] The difference between this group of comparative examples and Example 1 is that the content of the added inorganic fiber material is 2.0wt%, but the temperature when the fiber is added and the insulation time after the fiber is added are different, as shown in Table 8:
[0127] Table 8.
[0128]
[0129]
[0130] As can be seen from Table 8, when the amount of inorganic fiber added is 2.0wt%, the temperature when adding the fiber and the insulation time after adding the fiber will directly affect the fiber content in the final glass. After the glass in Comparative Examples 7-9 and Comparative Example 12 is illuminated, there are no abnormal light spots, indicating that the fiber is in an over-melted state and has no toughening effect. When the temperature when adding the fiber is too low (1300°C), the inorganic fiber is too low in temperature compared to the inorganic fiber melting point, resulting in the inorganic fiber being unable to form a molten softened state. After forming, a large fiber defect is formed in the glass, and the difference between its expansion and the matrix glass increases, which will increase the risk of glass breakage.
[0131] Comparative Examples 16-21
[0132] The difference between this group of comparative examples and Example 1 is that the content of the added inorganic fiber material is 2.0wt%, but the diameters of the added fibers are different, as shown in Table 9:
[0133] Table 9.
[0134]
[0135]
[0136] It can be seen from Table 9 that when the diameter of the added inorganic fiber material is less than 23 nm, or greater than 58 nm, it will affect the scratch resistance of the glass, and when the fiber diameter is too large, it will also affect the light transmittance of the glass.
[0137] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing fiber-reinforced transparent glass-ceramics, characterized in that: The maximum scratch width of the transparent glass-ceramics under a pressure of 1.0 Kg is less than 13.07 μm; the maximum scratch width under a pressure of 1.8 Kg is less than 22.25 μm; the maximum scratch width under a pressure of 2.3 Kg is less than 35.58 μm; The maximum scratch width is less than 51.17μm under a pressure of 2.8Kg; The preparation method comprises: Prepare raw materials according to the oxide formula, pour the raw materials into a mixer for mixing to obtain a mixed material, and determine whether the mixed material is homogenized by testing the conductivity of the mixed material; The homogenized mixed material is loaded into a platinum crucible, and then the platinum crucible is placed in a high-temperature lifting furnace, and the mixed material is kept warm at a melting temperature of 1500-1600° C. for the first stage, and then the temperature is lowered to 1400-1450° C. for the second stage, and 0.5-2.0wt% of inorganic fiber is added, and the mixture is kept warm again for 5-20 minutes after being stirred evenly, and then the temperature is lowered to 1300-1350° C. for the third stage to obtain a glass melt; After the glass melt is cast into shape, it is annealed, crystallized and chemically strengthened to obtain the transparent microcrystalline glass.
2. The method for preparing fiber-reinforced transparent glass-ceramics according to claim 1, characterized in that: The heating rate of the high temperature lifting furnace in the process of reaching the melting temperature of 1500-1600° C. is 5-10° C. / min, and the insulation time of the first stage is 2-3 hours.
3. The method for preparing fiber-reinforced transparent glass-ceramics according to claim 1, characterized in that: The time for the temperature in the high-temperature lifting furnace to drop from the melting temperature of 1500-1600° C. to 1400-1450° C. is 20-30 minutes.
4. The method for preparing fiber-reinforced transparent glass-ceramics according to claim 3, characterized in that: Before adding the inorganic fiber, the second stage heat preservation time is 0.5-1h; then the temperature is lowered to 1300-1350°C for the third stage heat preservation time of 5-10min.
5. The method for preparing fiber-reinforced transparent glass-ceramics according to any one of claims 1 to 4, characterized in that: The inorganic fiber is selected from any one or more of glass fiber, basalt fiber and zirconia fiber, and the diameter of the inorganic fiber is 20-50 nm.
6. The method for preparing fiber-reinforced transparent glass-ceramics according to claim 5, characterized in that: The annealing temperature is 500-550° C., and the holding time is 0.5-1 h.
7. The method for preparing fiber-reinforced transparent glass-ceramics according to claim 5, characterized in that: The crystallization treatment includes a nucleation stage and a crystallization stage. The temperature of the nucleation stage is 520-600° C. and the temperature is kept for 2-4 hours; the temperature of the crystallization stage is 700-800° C. and the temperature is kept for 3-5 hours.
8. The method for preparing fiber-reinforced transparent glass-ceramics according to any one of claims 1 to 4, characterized in that: The raw materials include quartz sand, aluminum oxide, soda ash, potassium carbonate, zirconium oxide, lithium carbonate, diammonium phosphate and sodium nitrate. The raw materials, calculated by mass percentage of oxides, include: <h2 style=";text-align:left;direction:ltr">SiO267-78%, Al2O35-10%, Na2O0 0.5-2.1%, K2O0 0.5-1.3%, ZrO24.5-8.1%, Li2O8.7-12.5%, P2O50.8-2.3%, NO3<h2 style=";text-align:left;direction:ltr"> - <h2 style=";text-align:left;direction:ltr"> 0.5-2%.
9. The method for preparing fiber-reinforced transparent glass-ceramics according to any one of claims 1 to 4, characterized in that: The test method for homogenizing the mixed material is as follows: randomly sample 3-5 portions of the mixed material, each portion is 10-20g, the samples are mixed with 100ml of pure water and stirred for 5-10min, the conductivity of each sample is tested, and the average value is calculated. If the difference between the conductivity of each sample and the average value is within the range of -0.25 to 0.25ms / cm, it indicates that the mixed material has been mixed evenly.
10. A fiber-reinforced transparent glass-ceramic, characterized in that: The transparent microcrystalline glass is prepared by the preparation method according to any one of claims 1 to 9; The maximum scratch width of the transparent microcrystalline glass under a pressure of 1.0 Kg is less than 13.07 μm; the maximum scratch width under a pressure of 1.8 Kg is less than 22.25 μm; the maximum scratch width under a pressure of 2.3 Kg is less than 35.58 μm; and the maximum scratch width under a pressure of 2.8 Kg is less than 51.17 μm.
Citation Information
Cited By
Transparent glass ceramic with tough zirconium oxide fibers and preparation method of transparent glass ceramic
CN120903837A